GROWTH AND PHOTOSYNTHETIC RESPONSE OF Capsicum annum L. EXPOSED TO SIMULATED ACID RAIN - I. S, ADAMU; A. A, UKAOMA; C. M, DURU; Z. A, ABDULLAHI; A. M, UMAR; M, ADAMU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Rain is inherently acidic, human anthropogenic activities including pollution from homes, companies, power plants, and car vehicles, which result in the release of molecules like Carbon dioxide, Nitric dioxide, and Sulfur dioxide, are making it more and more acidic. The screen house experiment was undertaken to assess how acid rain affects plants. In the lab, to create acid rain concentrated sulphuric acid (H2SO4) and concentrated nitric acid (HNO3) were mixed in a 2:1 ratio. The desired pH level was measured using a Duplex pH meter. The plant was simulated with acid rain (pH 2.5, 3.0, 3.5, and control 5.6) every three days for six weeks. ANOVA was used for the statistical analysis. The significance of the mean difference was assessed using Ducan's multiple-range tests. With increasing pH levels, plant height (FPepper = 63.835), leaf area (FPepper =60.965), stem girth (FPepper =39.3), the number of leaves (FPepper =34.265), relative growth rate (FPepper = 40.646), and chlorophyll content (FPepper = 4.6029, 7.8154, 36.746) decreased considerably (p<0.001). These findings advance our knowledge of how acid rain impacts urban vegetation and serves as a warning to limit acid rain production